2015
DOI: 10.1200/jco.2015.33.29_suppl.60
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of trust in the medical profession among cancer patients receiving palliative care: A preliminary study.

Abstract: Background: Trust influences healthcare through the willingness to seek care, disclose sensitive information, adhere to treatment, and satisfaction with care. Understanding factors that influence trust may help in physician-patient relationship particularly at end of life. Objectives: We explored the association between trust and other demographic and psychosocial factors. We also explored the performance of the single-item Degree of Trust scale (0 best to 10 worst) compared with the validated five-item Trust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…Changes at a similar scale have previously been associated with significant changes to clinical outcomes. [20][21][22][23][24][25] To better understand this improvement in scores across several dimensions, we measured whether these visits were associated with longer clinical encounters, noting that the mean estimated provider minutes available was 5.6 minutes higher for GPS Log In visits than No Log In visits (29.2 [9.1] vs. 23.6 [7.1]; P < 0.001). This suggests that physicians were more likely to use the GPS when more time was available for the encounter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes at a similar scale have previously been associated with significant changes to clinical outcomes. [20][21][22][23][24][25] To better understand this improvement in scores across several dimensions, we measured whether these visits were associated with longer clinical encounters, noting that the mean estimated provider minutes available was 5.6 minutes higher for GPS Log In visits than No Log In visits (29.2 [9.1] vs. 23.6 [7.1]; P < 0.001). This suggests that physicians were more likely to use the GPS when more time was available for the encounter.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has demonstrated that small changes to patient perceptions measured with similar survey tools can be associated with significant changes in clinical outcomes. [20][21][22][23][24][25] Trust and privacy findings were also intriguing. Trust scores, which measured a patient's belief that the provider had his or her best interest in mind when making clinical decisions, were not affected for the genotyped patients in this study by their providers' use of pharmacogenomics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age and sex have been shown to play a role in patient–physician trust in other studies which showed that older patients and patients who are sex congruent with his or her physician have higher trust 10,19 . In this cohort of 50 patients with head and neck cancer, age was not associated with differences in trust.…”
Section: Discussionmentioning
confidence: 50%
“…Existing data demonstrate that various factors can affect patients' trust in providers, including both intrinsic patient characteristics and various aspects of their interactions with providers. In one study of patients with a broad range of cancers, older, less depressed, and more hopeful patients were more likely to have trust in their physician 10 . These results have been corroborated by similar large‐scale studies in primary care 11,12 .…”
Section: Introductionmentioning
confidence: 70%